2018
DOI: 10.3390/f9010042
|View full text |Cite
|
Sign up to set email alerts
|

Branch Development of Five-Year-Old Betula alnoides Plantations in Response to Planting Density

Abstract: Branch development in the lower part of stem is critical to both early stem growth and wood quality of the most valuable section of tree, and its regulation through planting density has always been greatly concerned. Here the effect of planting density on branch development was examined in a five-year-old plantation of Betula alnoides with six planting densities (625, 833, 1111, 1250, 1667, and 2500 stems per hectare (sph)) in Guangdong Province, South China. Branch quantity (number, proportion, and density), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 39 publications
0
5
0
Order By: Relevance
“…Colin and Houllier [9] also observed that tree size (DBH) was the most effective predictor of maximum branch diameter. Other non-measured predictor variables may have improved our predictive model; branch length, stand density, and trees' social status can also play an additional role in predicting branch diameter [9,42]. Nevertheless, the R 2 of our model reached 0.72 based on our included predictor variables.…”
Section: Branch Diametermentioning
confidence: 77%
“…Colin and Houllier [9] also observed that tree size (DBH) was the most effective predictor of maximum branch diameter. Other non-measured predictor variables may have improved our predictive model; branch length, stand density, and trees' social status can also play an additional role in predicting branch diameter [9,42]. Nevertheless, the R 2 of our model reached 0.72 based on our included predictor variables.…”
Section: Branch Diametermentioning
confidence: 77%
“…In addition to pruning, the quality of the branches in birch stands can be influenced also by the selection of the regeneration material (Viherä-Aarnio and Velling 1999; Stener and Jansson 2005), site selection , and forest management, i.e., the stand density before and after pre-commercial and commercial thinning (Niemistö 1995a(Niemistö , 1997Mäkinen et al 2003). Dense spacing in young birch stands decreases the diameter increment of branches and facilitates their suppression, death, and self-pruning (Cameron et al 1995;Niemistö 1995a;Mäkinen 2002;Mäkinen et al 2003;Hynynen et al 2010;Wang et al 2015Wang et al , 2017Wang et al , 2018. Delay or negligence in thinning, on the other hand, clearly slows down the self-pruning of dead branches as well as the diameter increment of the birch trees (Niemistö 1997), thus reducing the volume of knot-free wood outside the knotty core.…”
Section: Applicability In Forest Practicementioning
confidence: 99%
“…Several studies have shown that increasing resources, including nutrient and light availability, increase tree and branch growth (Niinemets and Lukjanova 2003;Mäkinen and Hein 2006;Chen and Sumida 2018). Hence, current stem and wood properties relate to past tree growth, which is affected by geographical origin, site properties, stand dynamics and silvicultural regime (Auty et al 2012;Mäkinen et al 2015;Wang et al 2018). Studies have been published over the years that report the effects of stand density and thinning on branch properties for several tree species (Weiskittel et al 2009;Huuskonen et al 2014;Grace et al 2015).…”
Section: Introductionmentioning
confidence: 99%